The Informality Trap : Tax Evasion, Finance, and Productivity in Brazil - Kapaz, Emerson (World Bank, Washington, DC, 2012)
This Note highlights the adverse consequences of informality for private sector development and explains what governments can do about it. It uses new data from the World Bank's Investment Climate Survey in Brazil that show for the first time the extent of tax evasion and confirm that informal firms are less productive and less likely to access financial markets than other firms. It also provides some advice on how to tackle the problem-by emphasizing the benefits of regulatory compliance, reducing the costs of going formal, and tightening up enforcement.